Impulsive control of nonlinear systems with impulse time window and bounded gain error - Zou, Limin; Peng, Yang; Feng, Yuming; Tu, Zhengwen (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, we establish a new sufficient condition for the stability of impulsive systems with impulse time window and bounded gain error. The proposed result is more general and more applicable than some existing results. Finally, a numerical example is given to show the effectiveness of our result.